2020
DOI: 10.1007/s11629-019-5728-9
|View full text |Cite|
|
Sign up to set email alerts
|

Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018

Abstract: Glaciers in the northern Pakistan are a distinctive source of freshwater for the irrigation, drinking and industrial water supplies of the people living in those regions and downstream. These glaciers are under a direct global warming impact as indicated in many previous studies. In this study, we estimated the glacier dynamics in terms of Equilibrium Line Altitude (ELA), mass balance and the snout position variation using remote sensing data between 2001 and 2018. Six glaciers, having area ≥ 20 km2 each, situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…During the period 1866-2006, it has also reported that important declining tendencies in the monsoon precipitation (Bhutiyani et al, 2010). A periodic tendency analysis has shown an important rise in the temperature which may be the cause of glaciers terminus retreat (Gul et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…During the period 1866-2006, it has also reported that important declining tendencies in the monsoon precipitation (Bhutiyani et al, 2010). A periodic tendency analysis has shown an important rise in the temperature which may be the cause of glaciers terminus retreat (Gul et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Glaciers in mountainous area are the freshwater environment on this earth's and important component of universal stream ow cycles (Bajracharya et al, 2015;Gul et al, 2020).Water sources are mostly effected by the change of glacier dissolve over ow in the tall mountains including the Himalayas, Karakoram and Hindukush (HKH) (Agrawal, Thayyen, & Dimri, 2018;Gul et al, 2020). Mountain glaciers are the predominant water suppliers for large rivers (Naeem et al, 2016;Shrestha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Glacier melt from the watershed locality contributes meaningfully to the ow of River Chitral as it runs down the valley (Shamsuddin, 2020). Tirich Mir with a mean elevation of 7708 m (asl) is the highest peak and snow cover of the Hindukush region and is also situated in the catchment area of the Chitral river basin (Gul et al, 2020). The basin covers large to small size glaciers (Shakir et al, 2010).…”
Section: Study Areamentioning
confidence: 99%
“…For the changing trend of climate data temperature and precipitation, the nonparametric test Mann-Kendall trend test with Sen's Slope Estimator was used. It was used to estimate the magnitude of the trend for time series data (Ahmad et al, 2018;Gul et al, 2020;Hussain et al, 2015) for both variables.…”
Section: Climatic Effects On Mass Balancementioning
confidence: 99%
“…In the last two decades, glaciers in the Himalayan region retreated extensively [3], although it is still unclear which climatic variable is playing a significant role in glacier retreat. Glaciers are considered the prime source of climate change indicators [4]. The climate of the HKH region varies greatly and depends on two different climate regimes in which westerlies influence the northern and western parts while southern and eastern parts are influenced by monsoon [5].…”
Section: Introductionmentioning
confidence: 99%